Effect of Environmental Conditions on Energy Efficiency of AAC-based Building Envelopes - V. Koci; J. Madera; R. Cerny (Zenodo, 2012)
Calculations of energy efficiency of several AACbased building envelopes under different climatic conditions are presented. As thermal insulating materials, expanded polystyrene and hydrophobic and hydrophilic mineral wools are assumed. The computations are accomplished using computer code HEMOT developed at Department of Materials Engineering, Faculty of Civil Engineering at the Czech Technical University in Prague. The climatic data of Athens, Kazan, Oslo, Prague and Reykjavík are obtained using METEONORM software.